Influence of plastic strain localisation on the mechanical properties of metal matrix composites. (3rd June 2017) - Fan, Guohua; Wu, Hao; Geng, Lin; Zheng, Zhenzhu; Cui, Xiping; Hu, Dong
Abstract: The aim of the present study is to reveal the most critical underlying factor influencing the mechanical properties of metal matrix composites (MMCs). It is shown that the mechanical properties of MMCs are essentially governed by the degree of strain localisation during plastic deformation. In other words, the MMCs exhibit superior mechanical performance only if the strain localisation is obviously inhibited and the accumulated stresses can be effectively transferred out. The work provides a new perspective in guiding the design of next-generation high-performance MMCs by suppressing the strain localisation as far as possible.